Static and fatigue behaviour of trapezoid web plate girder - Izni Syahrizal Ibrahim 309898 (Skudai : Universiti Teknologi Malaysia, 2000)
Thesis (Master of Engineering) - Universiti Teknologi Malaysia, 2000